Discourse Analysis in Song Lyric Entitled Boulevard Sung by Dan Byrd - Wardhani, Niken; Sukarni, Semi; Sudar, Sudar (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2024)
This research aimed to get the three aspect of discourse analysis: contextual, grammatical and lexical aspect of the song lyric entitled Boulevard. In this study, the researcher would like to discuss the song lyric using qualitative approach. After analyzing it, the researcher found that the lyric was about a sad story of a heartbroken man and hoping to get a happy life with his lover if he got another chance. In the side of grammatical and lexical analysis give a cohession and coherence in the song lyric. The result of the grammatical and lexical aspect gives a depiction of cohesion and coherence of the song discourse of “Boulevard”. It can be seen that there are seven forms of first singular personal pronoun of “I”, nine forms of second plural personal pronoun of “you”, and three form of first plural personal pronoun of “we”. Though, it is difficult to find lexical aspect of this song discourse in the song lyric “Boulevard, there are collocation and equivalency aspect in it. They are “My love” and “lovers”, “happy forever” and “love together” as colocation aspect. Whereas “let me know” and “tell me”, “go” and “left” as the equivalency aspect.